Articulatory dynamics of laterals and trills in Tamil and Telugu: An Ultrasound Study - M, Irfana; Reddy, Sathya Santhoshini (Master Program in Linguistics, Diponegoro University, 2024)
Compared to other sounds, /l/ and /r/ have much more complex and more variable articulatory configurations across speakers. The present study aims to find the articulatory dynamics of lateral /l/ and trill /r/ across two Dravidian languages, i.e., Tamil and Telugu. A total of 20 subjects from two language groups were taken for the study, with 10 participants from each language, which includes an equal number of males and females. Tongue contours for each subject were taken for /l/ and /r/ sounds in the VCV context. In Tamil, the posterior tongue height was more for /r/, and there was no difference in height in the mid-region and anterior region. In the /u/ context, tongue height was more for /l/. The statistical analysis of /l/ and /r/ in Tamil revealed that in the /a/ context, there was no significant difference in tongue advancement and tongue height. The tongue height for /l/ was more in the anterior region when compared to the /r/, but there was no significant difference in tongue advancement in the /i/context. The present study findings will be provided information regarding the tongue dynamics of trills and laterals in normal individuals across two Dravidian languages.